Analysis of Salvinorin A in urine using microextraction in packed syringe and GC–MS/MS. (March 2013) - Moreno, Ivo; da Fonseca, Beatriz; Oppolzer, David; Martinho, Ana; Barroso, Mário; Cruz, Angelines; Queiroz, João António; Gallardo, Eugenia
Background: The aim of this work was to develop and validate a method for the determination of Salvinorin A in human urine using microextraction by packed sorbent (MEPS) and GC–MS/MS.Results: The technique uses a sample volume as low as 0.2 ml, and the analyte was extracted using a C18 sorbent. The method showed to be linear between 20 and 1000 ng/ml and presented a LOD of 5 ng/ml. Intra- and inter-day precision and accuracy were acceptable. Absolute recoveries ranged from 71 to 80%.Conclusion: GC–MS/MS with MEPS demonstrated to be a fast and simple procedure for the quantification of Salvinorin A in urine. This is the first time that GC–MS/MS with MEPS was used for the determination of this compound in biological fluids. Furthermore, the device could be reused for up to 80 extractions, which accounted for a lower cost of analysis.